PENGEMBANGAN MODEL TRANSPORTASI SEIMBANG (BALANCE) DENGAN MODIFIED DISTRIBUTION (MODI) DENGAN ORDO 5X5 BERBASIS ANDROID - Indrianingsih, Yuliani; Nugraheny, Dwi; Putra, Dwi Andhika (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2017)
The absence of rapid examination technique to study transportation model using Modified Distribution often learning process become less efficient and effective. To use Modified Distribution (MODI), the first must to found the first solution of transportation model. To find the first solution of this transportation model using Northwest Corner method then find optimum solution with Modified Distribution (MODI) method. Before that Modified Distribution method had built to application on desktop with [9], but it just to calculate optimum solution to find minimum cost of transportation model on matrix 3X3. On application have some suggestion for developer who want to develop it, like to change user interface to be interesting, expand matrix to m X n (for example 5X5) and add some study case in application to guide user to done case of Operation Research to calculate optimum solution to find minimum cost on transportation model using Modified Distribution (MODI) method in the class. In this essay will be develop an application Modified Distribution (MODI) using Northwest Corner method to calculate first solution and Modified Distribution (MODI) to calculate optimum solution with matrix 5X5 which implemented on android in operating system minimum API 15: Android 4.0.3 (Ice Cream Sandwich). Application Modified Distribution (MODI) have interesting interface, give easy to access information, and get accurate results, this is established from testing with score average 83,77%.